LncRNA ELF3-AS1 inhibits gastric cancer by forming a negative feedback loop with SNAI2 and regulates ELF3 mRNA stability via interacting with ILF2/ILF3 complex - Dandan Li; Li Shen; Xudong Zhang; Zhen Chen; Pan Huang; Congcong Huang; Shanshan Qin (Journal of Experimental & Clinical Cancer Research, 2022)
Abstract Background The biological function of lncRNA ELF3-AS1 remains largely unknown in cancers. The cause of SNAI2 overexpression in tumor metastasis remains largely unclear. The molecular mechanisms underlying the high co-expression of antisense lncRNAs and adjacent protein-coding genes remains unclear. Methods RNA-seq, CHIP and dual-luciferase reporter assay were performed to identify lncRNAs regulated by SNAI2. MicroRNA-seq and RNA-seq studies were conducted to reveal the biological function of ELF3-AS1 in GC. RNA pulldown and CHIRP assays were conducted to identify the protein that interacts with ELF3-AS1. Results A total of 123 lncRNAs were identified to be regulated by SNAI2 in GC by RNA sequencing. The ELF3 gene and antisense lncRNA ELF3-AS1 were both transcriptionally repressed by SNAI2 or SNAI1. Down-regulation of ELF3-AS1 and ELF3 predicted poor prognosis in GC. Nuclear localized lncRNA ELF3-AS1 negatively regulated GC cell cycle progression via suppressing G1/S transition and histone synthesis. ELF3-AS1 mainly inhibited GC metastasis by repressing SNAI2 signaling. Additionally, ELF3-AS1 modulated ELF3 mRNA stability by RNA-RNA interaction. The RNA duplexes formed by ELF3 mRNA and lncRNA ELF3-AS1 directly interacted with the double-stranded RNA (dsRNA) binding protein complex ILF2/ILF3 (NF45/NF90). In turn, the ILF2/ILF3 complex dynamically regulated the expression of ELF3-AS1 and ELF3 by affecting the dsRNA stability. Conclusions The SNAI2-ELF3-AS1 feedback loop regulates ELF3 expression at transcriptional and post-transcriptional levels and drives gastric cancer metastasis by maintaining SNAI2 overexpression. The ILF2/ILF3 complex plays a critical role in regulating dsRNA stability. In addition, our work provides a direct evidence that head-to-head antisense lncRNAs can share promoters with neighboring coding genes, which make their expression subject to similar transcriptional regulation, leading to high co-expression.